2001
DOI: 10.3189/172756401781818950
|View full text |Cite
|
Sign up to set email alerts
|

Time-series observations of the structure and properties of brackish ice in the Gulf of Finland

Abstract: The Baltic Sea is a semi-enclosed brackish water basin where sea ice occurs annually. The sea-ice study discussed here was conducted as a Finnish-Japanese cooperative research programme entitled "Ice Climatology of the Okhotsk and Baltic Seas’’ to investigate the structure and properties of the brackish ice in the Baltic Sea. Ice, snow and water samples were collected at Santala Bay, near the mouth of the Gulf of Finland, once a week from 20 January to 12 April 1999. The salinity and oxygen isotopic compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 10 publications
7
56
0
Order By: Relevance
“…4), since melting and refreezing of snow are essential for the formation of superimposed ice. The results correspond to observations made in the northern Baltic Sea by Kawamura et al (2001), although they found more negative d…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…4), since melting and refreezing of snow are essential for the formation of superimposed ice. The results correspond to observations made in the northern Baltic Sea by Kawamura et al (2001), although they found more negative d…”
Section: Discussionsupporting
confidence: 91%
“…The d 18 O signature of the White Sea can be assumed to be less negative, due to a lowered freshwater input compared to the Baltic Sea. Furthermore, Kawamura et al (2001) did not find such strong melting of the columnar portion, which can be attributed to a lower freezing point, since salinity in the White Sea is considerably higher than that of the Baltic Sea (2-4), or a higher heat flux from underlying water, as proposed by Lytle and Ackley (2001). These authors also found a complete melt-down of the columnar ice portion.…”
mentioning
confidence: 84%
“…The ice texture of Core A was determined by thin-section analysis (e.g. Kawamura et al 2001). Based on ice crystal size and orientation, 3 stratigraphic units were distinguished: granular ice, columnar ice and intermediate granular/columnar ice (Eicken & Lange 1989).…”
Section: Methodsmentioning
confidence: 99%
“…5) often assumed to be a characteristic feature of superimposed ice (e.g. Kawamura andothers, 1997, 2004;Haas and others, 2001). The structure was more like that of snow ice with a rather fine-grained structure (see Fig.…”
Section: Observations On Surface Granular Ice Layer Developmentmentioning
confidence: 98%